Unilateral biportal endoscopy for the treatment of symptomatic spinal epidural lipomatosis: a case report and literature review - Li, Yahao; Guo, Hong; Li, Zihang; Wang, Yucheng; Tang, Zhenyu; Li, Hongwei; Jiang, Hong; Liu, Jintao; Dai, Yuxiang; Zhu, Guangye; Yu, Pengfei (Frontiers in Surgery, 2025)
BackgroundSpinal epidural lipomatosis (SEL) is rare and often ignored or misdiagnosed. Traditional open surgery is considered the standard procedure for treating symptomatic SEL. However, open surgery is often associated with substantial trauma and a long recovery period.Case presentationA 37-year-old female patient was diagnosed with SEL and underwent unilateral biportal endoscopy (UBE) after failure of conservative treatment. The surgery was performed successfully with an estimated blood loss of 20 ml and a whole operation time of 60 min. The patient experienced significant relief of her neurologic symptoms and was discharged 2 days postoperatively. She reported no symptoms other than mild weakness of the low back at the last follow-up 12 months postoperatively. UBE may be an effective alternative to open surgical treatment for symptomatic SEL with the advantages of minimal invasion and quick recovery.ConclusionsSEL is not restricted to the commonly involved lumbosacral region and may occur in other segments of the spine, which should be considered during diagnosis. The advantages of UBE for treating SEL, including minimal invasiveness, muscle preservation, rapid recovery, clear visualization, and effective decompression, make it a viable surgical option; however, its long-term efficacy and safety require further validation.